Hubungan Antara Kepuasan Pelatihan dan Motivasi Kerja Karyawan di Unit IGD Ciputra Hospital Surabaya - Efendi, Denny (Asosiasi Ahli Administrasi Indonesia, 2025)
Training is one of the organizational efforts to enhance employee competence and work motivation. This study aims to examine the relationship between training satisfaction and work motivation among employees in the ED unit of Ciputra Hospital Surabaya. A quantitative approach with a cross-sectional design was employed. A total of 30 respondents were selected using total sampling. The instrument used was a Likert-scale questionnaire. Data were analyzed using Spearman's correlation test, as the data were not normally distributed (p < 0.05 in the Shapiro-Wilk test). The results revealed a strong and significant relationship between training satisfaction and work motivation (ρ = 0.584; p < 0.001). It can be concluded that higher training satisfaction correlates with higher work motivation. This study recommends improving training quality as part of human resource development strategies. This study provides both theoretical and practical implications. Theoretically, it supports the Two-Factor Theory of Herzberg and Self-Determination Theory by Deci and Ryan, showing that satisfaction with training can enhance intrinsic motivation. Practically, this research offers evidence for hospital HR departments to design more engaging and relevant training. The novelty of this research lies in its focus on the Emergency Department setting a high-pressure work environment rarely studied in this context within Indonesian hospitals.